Кількісний і якісний склад каннабіноїдних сполук та їх співвідношення у сортів конопель Cannabis sativa L. - Богданова, А.С.; Горшкова, Л.М. (Фактори експериментальної еволюції організмів, 2016)
Aim. With the aim of creating highly productive with the considerable content of cannabinoid the necessity of applying species with the high level of cannabidiol in the selective work emerges. The influence of different soil and climate zones on the biosynthesis of these compounds should be researched. Мethods. The quantitative and qualitative analysis of the cannabinoid compounds was held with the help of the gas and liquid chromatograph Hewlett Packard 5830 A. The content of cannabinoids was defined with the integrator Hewlett Packard 3380 A. Results. The results of the quantitative and qualitative analysis proved that the cannabis species Hlukhivs’ka 10 and YUSО-1 synthesized larger amount of cannabidiol compared to tetrahydrocannabidiol content. Species YUS-6, South Cherkas’ki and Dniprovs’ki 4, except the north eastern region, had mostly identical content of cannabidiol and tetrahydrocannabidiol. Conclusions. Quantity and quality content of cannabidiol and tetrahydrocannabidiol was genetically conditioned. The external conditions of different soil and climate zones facilitated the realization of the specie’s potential. The level of accumulating the separate compounds in the cannabis species is defined by the complex of the zone conditions which favoured the specie’s genetic potential. Keywords: cannabinoids, cannabidiol, tetrahydrocannabidiol, cannabis.